Alpha-Particle Generation from H-11B Fusion Initiated by Laser-Accelerated Boron Ions. (26th September 2022) - Kong, Defeng; Xu, Shirui; Shou, Yinren; Gao, Ying; Mei, Zhusong; Pan, Zhuo; Liu, Zhipeng; Cao, Zhengxuan; Liang, Yulan; Peng, Ziyang; Wang, Pengjie; Luo, Di; et al.
Abstract : Here, we report the generation of MeV alpha-particles from H- 11 B fusion initiated by laser-accelerated boron ions. Boron ions with maximum energy of 6 MeV and fluence of 10 9 /MeV/sr@5 MeV were generated from 60 nm-thick self-supporting boron nanofoils irradiated by 1 J femtosecond pulses at an intensity of 10 19 W/cm 2 . By bombarding secondary hydrogenous targets with the boron ions, 3 × 10 5 /sr alpha-particles from H- 11 B fusion were registered, which is consistent with the theoretical yield calculated from the measured boron energy spectra. Our results demonstrated an alternative way toward ultrashort MeV alpha-particle sources employing compact femtosecond lasers. The ion acceleration and product measurement scheme are referential for the studies on the ion stopping power and cross section of the H- 11 B reaction in solid or plasma.